Post liver transplant recurrent and de novo viral infections - Jothimani, Dinesh (Best Pract Res Clin Gastroenterol, 2020)
Survival following liver transplantation has changed dramatically owing to improvement in surgical techniques, peri-operative care and optimal immunosuppressive therapy. Post-Liver transplant (LT) de novo or recurrent viral infection continues to cause major allograft dysfunction, leading to poor graft and patient survival in untreated patients. Availability of highly effective antiviral drugs has significantly improved post-LT survival. Patients transplanted for chronic hepatitis B infection should receive life-long nucleos(t)ide analogues, with or without HBIg for effective viral control. Patients with chronic hepatitis C should be commenced on directly acting antiviral (DAA) drugs prior to transplantation. DAA therapy for post-LT recurrent hepatitis C infection is associated with close to 100% sustained virological response (SVR), irrespective of genotype. De novo chronic Hepatitis E infection is an increasingly recognised cause of allograft dysfunction in LT recipients. Untreated chronic HEV infection of the graft may lead to liver fibrosis and allograft failure. CMV and EBV can reactivate leading to systemic illness following liver transplantation. With COVID-19 pandemic, post-transplant patients are at risk of SARS-Co-V2 infection. Majority of the LT recipients require hospitalization, and the mortality in this population is around 20%. Early recognition of allograft dysfunction and identification of viral aetiology is essential in the management of post-LT de novo or recurrent infections. Optimising immunosuppression is an important step in reducing the severity of allograft damage in the treatment of post-transplant viral infections. Viral clearance or control can be achieved by early initiation of high potency antiviral therapy.